Language Isolation of the Slovenian Language in Immigrant Communities. The Example of the Slovenian Community in Toronto - Kralj, Tadej (Slavia Centralis, 2024)
The Slovenian Community in Toronto has existed since the 1950s, when the members of the community began to associate in Slovenian churches (Our Lady Help of Christians, Our Lady of the Miraculous Medal Parish), where they participated in activities of various societies and so preserved the Slovenian language that they used when they left their home country. In the new environment, the members mostly used the Slovenian language with their families and within the Slovenian community. Consequently, the language they used did not change in the same manner as it did in the home country. The purpose of the article is to present the isolation of the Slovenian language as a heritage language. In the everyday communication of 1st (and also 2nd) generation members of the community this can be observed in the use of the so called preserved language, namely the use of archaic vocabulary which is no longer used in present-day Slovenia. The symbolic function of the Slovenian language as a heritage language is also seen in the preservation of folk songs and prayer forms as a preserved tradition.